Validation of Patient‐Reported Outcomes Measurement Information System® ( PROMIS ®) Pediatric Measures for Children with Chronic Nonbacterial Osteomyelitis - Mary M. Eckert; Eveline Y. Wu; Melissa Oliver; Joshua Scheck; Sivia Lapidus; Ummusen Kaya Akca; Shima Yasin; Aleksander Lenert; Sara Stern; Antonella Insalaco; Manuela Pardeo; Gabriele Simonini; et al. (Arthritis Care & Research, 2026)
Objectives To assess the validity of the Patient‐Reported Outcomes Measurement Information System® (PROMIS®) Pediatric measures in patients with chronic nonbacterial osteomyelitis (CNO). Methods Within the longitudinal patient registry of CNO, English‐speaking patients aged 8 years and older self‐reported PROMIS Pediatric measures of fatigue, pain interference (PI), pain behavior (PB), mobility, upper extremity (UE), physical activity (PA) and strength impact (SI), and external validation measures. Log‐transformed linear mixed‐effects models with random patient intercepts were used to assess PROMIS T‐score changes. Wilcoxon signed‐rank test was performed to determine the PROMIS T‐score changes among the improved, worsened, and unchanged groups. Spearman rank correlation test determined the relationship of PROMIS T‐scores with disease status reported by patients/families. Results More than 1,000 clinical visits from 184 patients included PROMIS Pediatric measures entries. All PROMIS T‐scores correlated significantly (p